Mapping the Evolution of Arabic Language Education Research through Bibliometric Analysis in the Scopus Database (1980-2023) - Thoyib, Fachri Muhammad; Apriantoro, Muhammad Subhi; Maksum, Muh Nur Rochim; Jinan, Mutohharun (Universitas Muhammadiyah Surakarta, 2023)
Objective: The objective of this research is to analyze the evolution and trends in Arabic Language Education Research as documented in Scopus-indexed publications. Methodology: A bibliometric analysis approach was employed to investigate publications on Arabic Language Education within the Scopus database, spanning the period from 1980 to 2023. The analysis involved utilizing Excel and R/R-Studio, with VOSviewer employed for visualizing the co-occurrence of keywords and document citations. A total of 576 publications meeting specified criteria were identified. Findings: The study reveals an annual growth rate of 9.26%, reaching its peak in 2021 with the highest number of publications on Arabic Language Education. The United States, particularly with affiliations from the International Islamic University Malaysia, emerges as the leading contributor to these publications. Notably, Shohamy, E stands out as the most prolific author in the field. Implications/Novelty/Significance: This research provides a concise overview of the literature available to educators and researchers in the field of education, offering insights and recommendations for future research endeavors.